CRITICISM EVOLUTION IN ROMANIAN MUSICAL PERIODICALS: FROM GAZETA TEATRULUI NAȚIONAL (1835-1836) TO MUZICA (1908–PRESENT) - ŞUTEU, Cristina (Studia Universitatis Babes-Bolyai Musica, 2019)
The present study aims to analyse the publications that preceded the Muzica Journal [The Music], with a focus on their critical evolution: Gazeta Teatrului Național [National Theatre Journal, 1835-1836], Musicul român [Romanian Music, 1861], Eco musicale di Romania [1869-1871], Lyra română [Romanian Lyra, 1879-1880], Arta [The Art, 1883-1885, 1894-1896], Doina [The Doina, 1884-1886], Musa română [Romanian Muse, 1888, 1894-1895, 1906-1907], Romănia musicală [Musical Romania, 1890-1904]. I will also emphasize their bibliographic aspects and the references to musical criticism, where appropriate. I will present the bibliographic details of the Muzica Journal (1908-1910, 1916; 1919-1923, 1925; 1950-present), as well as the musical criticism references of the same publication.